FRI0424 Accessibility To Biological Therapy for Patients with Ankylosing Spondylitis in Romania Is Influenced by Area of Residence, Socio- Economic and Demographic Factors. (15th July 2016) - Enache, L.; Codreanu, C.; Mogosan, C.; Gutoiu, G.; Popescu, C.; Parvu, M.; Rednic, S.; Ionescu, R.
Abstract : Background: The efficacy of anti TNFblockers in active ankylosing spondylitis (AS) is widely accepted. In Europe, high costs related to biological treatment lead to significant differences regarding the patient's accessibility to treatment depending on the level of economic development of different countries. In Romania, according to the national reimbursement protocol, a patient is eligible for treatment with TNF blockers if the disease is active despite using at least two non-steroidal anti-inflammatory drugs and sulfasalazine (for peripheral arthritis). Objectives: The aim of the study is to assess the accessibility of patients with AS to biological therapy in Romania, depending on their area of residence and socio- economical indicators for each region. Methods: A cross-sectional study was performed in 41 counties and Bucharest. Data were collected from the Romanian Registry of Rheumatic Diseases and the socio- economic indicators from the yearbook of the National Institute for Statistics. Results: Data were gathered for 2013 AS patients treated with biologics. The mean age was 45.46 yrs (±12.07), 78% were male, 71% live in urban residences and the mean disease duration was 11.53 yrs. 74% (n=1498) of patients had access to biologics in their county of residence, while 26% (n=524) of patients had to travel for treatment to another county. Compared to the group treated inside their county of residence, those treated outside, originated from areas with a lower gross domestic product per capita (5701.77 € compared to 8722.44 €; p<0.001; t test) and with high deficit of physicians (1.28 physicians/ 1000 inhabitants, comparated to 2.63 physicians/ 1000 inhabitants; p<0.001; t test). The urban habitat was associated with a higher accessibility to biologics (75.9%) inside their county of residence compared to patients living in rural areas (69.2%) (p=0.002, χ 2 test); so the latter have to travel in order to being cared by a rheumatologist. The patients' age had a great influence on the accessibility to biologics: the patients treated outside of their county of residence were younger than those treated inside (44.1 yrs compared to 45.9 yrs; p=0.003, t test). On a national scale, the majority of AS patients treated outside their county of residence (86%; 449); were treated in Bucharest (the capital city); so the majority of patients treated with biologics in Bucharest are originating from other counties (60%; n=449/751). Conclusions: In Romania, although there is a national protocol for biological therapy in AS, applied in the same way in every region of the country, the accessibility to biologic therapy varies a lot, mostly due to differences in the socio- economic status of each area of residence. Disclosure of Interest: None declared